Anti‐huCD20 Antibody Therapy for Antibody‐Mediated Rejection of Renal Allografts in a Mouse Model. Issue 5 (2nd March 2015) - Abe, T.; Ishii, D.; Gorbacheva, V.; Kohei, N.; Tsuda, H.; Tanaka, T.; Dvorina, N.; Nonomura, N.; Takahara, S.; Valujskikh, A.; Baldwin, W. M.; Fairchild, R. L.
Abstract : We have reported that B6.CCR5 −/− mice reject renal allografts with high serum donor‐specific antibody (DSA) titers and marked C4d deposition in grafts, features consistent with antibody‐mediated rejection (AMR). B6.huCD20/CCR5 −/− mice, where human CD20 expression is restricted to B cells, rejected A/J renal allografts by day 26 posttransplant with DSA first detected in serum on day 5 posttransplant and increased thereafter. Recipient treatment with anti‐huCD20 mAb prior to the transplant and weekly up to 7 weeks posttransplant promoted long‐term allograft survival (>100 days) with low DSA titers. To investigate the effect of B cell depletion at the time serum DSA was first detected, recipients were treated with anti‐huCD20 mAb on days 5, 8, and 12 posttransplant. This regimen significantly reduced DSA titers and graft inflammation on day 15 posttransplant and prolonged allograft survival >60 days. However, DSA returned to the titers observed in control treated recipients by day 30 posttransplant and histological analyses on day 60 posttransplant indicated severe interstitial fibrosis. These results indicate that anti‐huCD20 mAb had the greatest effect as a prophylactic treatment and that the distinct kinetics of DSA responses accounts for acute renal allograft failure versus the development of fibrosis. Abstract : This study tests CD20‐specific antibody therapy in a mouse renal allograft model of antibody‐mediated rejection and shows long‐term allograft survival with peritransplant treatment, but development of graft fibrosis, tubular atrophy, and glomerulopathy when treatment is delayed until the time antibody is first detected.